Efektivitas Peran Baitul Maal Wat Tamwil dalam Mengatasi Praktik Rentenir pada BMT Itqan Kota Bandung - Nisa Srimulyani; Alda Salsa Achiri Pebriani; Dewi Rahmi (ITB AAS INDONESIA Surakarta, 2022)
This research was conducted to find out and discuss more deeply about the effectiveness of the role of BMT Itqan in Bandung in overcoming the practice of moneylenders, the effectiveness here is seen from the level of success or failure of the role of BMT Itqan in Bandung in overcoming the practice of moneylenders is shown by indicators, namely (1) Target Accuracy, (2) Member Perception, and (3) Program Socialization. The research method used is to distribute questionnaires to 100 active members of BMT Itqan Bandung. The results of the questionnaire obtained were then tested for validity through validity and reliability tests using the IBM SPSS Statistics Version 26. The data analysis technique used in this study was descriptive statistical techniques. The results showed that all indicators that determine the effectiveness of the role of Itqan BMT in overcoming the practice of moneylenders are stated in the very effective category. These indicators are (1) Targeting Accuracy with a percentage of 81.56% which is included in the very effective category, (2) Member Perceptions with a percentage of 82.42% which is included in the very effective category, (3) Program Socialization with a percentage of 82 .16% which is included in the very effective category.